2016
DOI: 10.1093/europace/euw139
|View full text |Cite
|
Sign up to set email alerts
|

Reduction of radiation exposure in cryoballoon ablation procedures: a single-centre study applying intracardiac echocardiography and other radioprotective measures

Abstract: Radiation exposure in CB PVI can be markedly reduced without prolonging procedure times, affecting the outcome or complication rates. Moreover, ICE seems to shorten total freezing time.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
40
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 17 publications
(42 citation statements)
references
References 20 publications
2
40
0
Order By: Relevance
“…The significant reduction in fluoroscopy time demonstrated in the main analysis was robust in all sensitivity testing, including studies with only AF patients (Hedges' g −1.25; 95% CI −2.14 to −0.36; P < .01) 10,11,24,26–31,37,38 . (Table S3).…”
Section: Resultsmentioning
confidence: 78%
See 4 more Smart Citations
“…The significant reduction in fluoroscopy time demonstrated in the main analysis was robust in all sensitivity testing, including studies with only AF patients (Hedges' g −1.25; 95% CI −2.14 to −0.36; P < .01) 10,11,24,26–31,37,38 . (Table S3).…”
Section: Resultsmentioning
confidence: 78%
“…Ten studies reported fluoroscopy dose data, with significant heterogeneity among studies (I 2 = 93%) and no evidence of publication bias or small study effects 23–28,31,33,37,38 . Use of ICE in ablation procedures showed significant reductions in fluoroscopy dose vs ablation without the use of ICE (Hedges' g −1.27; 95% CI −1.91 to −0.62; P < .01) (Figure 3A).…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations